Ameliorative Effect of Curcumin Nanoparticles against Monosodium Iodoacetate-Induced Knee Osteoarthritis in Rats - Hadeer M. Hamdalla; Rasha R. Ahmed; Sanaa R. Galaly; Ibrahim A. Naguib; Badrah S. Alghamdi; Osama M. Ahmed; Ahmed Farghali; Manal Abdul-Hamid (Hindawi Limited, 2022)
Aim. This study is aimed at evaluating the use of curcumin-loaded polylactic-co-glycolic acid nanoparticles (CUR-loaded PLGA NPs) as a treatment against monosodium iodoacetate- (MIA-) induced knee OA. Materials and Methods. Eighteen rats were assigned to three groups (n=6), namely, normal control group that received intra-articular injections (IAIs) of saline, an OA control group that received an IAIs of MIA (2 mg/50 μL), and a treatment group (MIA+CUR-loaded PLGA NPs) that received IAIs of CUR-loaded PLGA NPs (200 mg/kg b.wt). Results. The CUR NP treatment against knee OA alleviated radiographic alternations and histopathological changes and inhibited the upregulation in the serum levels of interleukin-1β, tumor necrosis factor-α, interleukin-6, and transforming growth factor-beta and the downregulation in interleukin-10. CUR NP-treated joints also decreased the mRNA expression of nuclear factor-kappa B and inducible nitric oxide synthase and the protein expression of matrix metalloproteinase-13 and caspase-3. Finally, CUR-loaded PLGA NP treatment mitigated the loss of type II collagen, which resulted in a significant reduction in malondialdehyde level and increased the glutathione content and superoxide dismutase activity compared with that of the OA group. Conclusion. This study demonstrated that the administration of CUR NPs could provide effective protection against MIA-induced OA and knee joint histological deteriorated changes due to its anti-inflammatory, antioxidant, and antiapoptotic properties.